A note on the tolerance range of Domortiera hirsuta (Sw.) Nees cytoforms on Mount Kinabalu - M.J. Loo; Monica Suleiman; Mariam Abd Latip, Datin (Forest Research Centre, Sabah Forestry Department, 2005)
Dumortiera hirsuta (Figures 1, 2 & 3) is a complex plant and has three levels of ploidy or cytoforms (Loo et al. 2005). It has athin and green thallus. The midrib of the thallis is obvious and the dorsal part is covered by “spider web” (So 1995). Appendix 1 shows the ecophysiological data recorded for 15 samples of D. hirsute, by using altimeter (altitude), luxmeter (light intensity), whirling psychrometer (relative humidity) and thermometer (air temperature).